Cooking class–based learning for fine motor skill development in early childhood education - Eti Hadiati; Febby Lian (Journal of Childhood and Elementary Studies, 2025)
Background: Fine motor skills are essential for early childhood development, as they support children’s readiness for academic learning, self-care, and independent functioning. Fine motor development requires meaningful, repetitive, and developmentally appropriate stimulation. However, learning practices in early childhood classrooms often remain academically oriented and provide limited opportunities for manipulative and experiential activities. Cooking class–based learning offers a play-based and contextual approach that integrates motor activity, engagement, and social interaction. Aims: This study aims to improve the fine motor skills of children aged 5–6 years through the implementation of cooking class–based learning in early childhood education. Method: This study employed a Classroom Action Research design based on the Kemmis and McTaggart model, conducted in two action cycles. The participants were 15 children aged 5–6 years at PAUD Kartini Jatimulyo, South Lampung. Data were collected through observation, interviews, and documentation focusing on manipulative skills, hand–eye coordination, and learning engagement. Data were analyzed using qualitative descriptive techniques through data reduction, data display, and conclusion drawing. Results: The findings show a gradual and substantial improvement in children’s fine motor skills across the research cycles. The proportion of children categorized as Very Well Developed increased significantly in Cycle II, while no children remained in the Not Yet Developed category. Cooking class activities enhanced children’s coordination, precision of hand movements, and active participation during learning. Conclusion: Cooking class–based learning effectively improves fine motor skills in early childhood education. Experiential and play-based activities supported by reflective teaching practices contribute to meaningful motor development and positive learning experiences.